Optimization of FinFET’s Fin Width and Height with Self-heating Effect - Lee, Gyeong Jae; Kwon, Yoon Jun; Song, Young Suh; Kim, Hyunwoo; Kim, Jang Hyun (Journal of Semiconductor Technology and Science, 2024)
—In this paper, we investigated the optimization of the fin width and height with an effective width of 40 nm under the conditions considering self-heating effect (SHE) through TCAD simulation. To ensure the reliability, calibration is performed with transfer curves based on experimental data. We demonstrate the region of device characteristic inversion caused by the difference in thermal resistance based on the variation in the area of heat dissipation for various fin widths. As a result, it is found that a fin width of 10 nm, which is neither too narrow nor too wide, is less affected by SHE.
Keywords: Fin height; Fin widths; FinFETs; Index terms; Index term—FinFET; Lattice-temperature; Optimisations; Self-heating effect; Thermal; Index Terms—FinFET; Lattice temperature; SHE; thermal conductivity; thermal resistance